Strategi Pengawasan Bawaslu Dalam Pemilu 2024 - Materu, Muhammad Alvin; Wijayanto, Hendra; Prasetyo, Sisman; Lukiyana, Lukiyana; Ahmad, Masnia (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2024)
Elections have become the biggest event every 5 years and are a manifestation of the implementation of the 4th precepts of the Pancasila and the 1945 Constitution, whereby every citizen has the right to vote in the democratic arena every 5 years and implementing organizations are required to oversee these activities. According to (Christian, 2020) organizational strategy refers to the goals to be achieved, a conducive work environment, and actions to deal with existing problems. Bawaslu as a supervisory organization must oversee the course of the upcoming election, in the previous election there was still fraud that occurred in several polling stations in Indonesia such as; ballot papers that have been punched and voted for by minors, so there needs to be an effort or action from the election supervisors to overcome this and in its implementation it is expected to involve the participation of the community in election supervision. Bawaslu conducts outreach to the public, especially inviting the public to actively participate as participatory supervisors, the participatory task is to properly monitor the 2024 election, if there is fraud, report it immediately to the officer. It can be concluded that the synergy between Bawaslu employees in the formulation and socialization of the 2024 election strategy is proceeding as it should. Bawaslu will take firm action against prospective leaders who are found to have committed election fraud or bribed the public to vote for themselves in accordance with statutory procedures and regulations. run for re-election in the next election.